Decreasing the Rate of Natural Decline in Apple Storage in Controlled Gas Environment Warehouses - Zokirovich, Zokirov Zoir (American Journal of Biology and Natural Sciences, 2025)
This article describes the results of studies on the agrobiological characteristics of apple varieties suitable for storage. Here, the main indicators of the apple varieties selected for the experiments were analyzed. As a result of the research, scientifically based conclusions were made.